Realizing Aboriginal Administrative Law - Promislow, Janna; Metallic, Naiomi (Administrative law in context, 2022)
"Administrative Law in Context, 4th Edition continues this title's approach to administrative law in the important contexts that shape legal ideas and doctrines in this field. It examines key principles and cases by leveraging the distinct voices of leading scholars and instructors from across Canada including an analysis of the recent Vavilov trilogy of cases from the Supreme Court of Canada and their significant affect on how judicial reviews of administrative decisions are now conducted in Canada. This detailed, collaborative analysis gives students a better sense of how administrative boards and tribunals work in practice and differentiates itself from Admin8 by using a contemporary experiential pedagogy that employs increased commentary and discussion."-- Provided by publisher.